PREVALENCE AND RISK FACTORS FOR PUERPERAL SEPSIS AT THE PUMWANI MATERNITY HOSPITAL. (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2020)
Introduction: Puerperal sepsis is the third most common cause of maternal mortality worldwide. It remains  one of the leading preventable causes of maternal mortality. Given its significant burden in terms of  morbidity, mortality and healthcare costs, studies on hospital specific incidences and patterns are important  to help inform policy for its prevention and management. The aim of this study was to determine the  prevalence and factors associated with puerperal sepsis at Pumwani Maternity Hospital, Kenya.  Methodology: We conducted a case-cohort study among post partum women admitted at Pumwani  Maternity Hospital. Eligible women were invited to respond to a verbal researcher administered  questionnaire assessing medical and obstetric history. Those recruited, were each called at day 7 and day  14 postpartum and asked a standard set of questions related to infection-related symptoms. In addition, all  enrolled women who attended a postnatal follow up visit at 14 days postpartum were reviewed, using a  history and clinical examination. The data was analysed to identify potential maternal risk factors associated  with occurrence of puerperal sepsis. Results: Seven hundred and ninety three postnatal mothers at Pumwani maternity hospital were recruited,  of which 566 women responded at two weeks postpartum. Sixty nine women among the 566 met the criteria  for puerperal sepsis. This corresponded to a prevalence of 12.2% at two weeks postpartum (95% CI 9.5 –  14.9%). Further analysis was done using 69 cases; each with 3 randomly selected controls. No deaths were  reported. Risk factors included labour lasting >24hours, caesarean section, obstructed labour, and multiple  vaginal examinations. Conclusion: The prevalence of puerperal sepsis in this cohort at two weeks postpartum at Pumwani  Maternity Hospital was at 12.2%(95% CI 9.5-14.9). Two or more vaginal examinations, prolonged and  obstructed labour, and Caesarean section were found to be significantly associated with increased odds of  puerperal sepsis. Appropriate measures like appropriate infection prevention protocols should be utilized in  order to prevent avoidable complications of labour and delivery that can lead to puerperal sepsis.